Four “Hidden” Poems by Kavafis - Castillo Didier, Miguel (Byzantion Nea Hellás, 2023)
Two problems are briefly presented here, around the reading of four “repudiated” poems by Kavafis: the one shown by the texts written in the archaic language and the fact that the poet left very valuable poems forgotten or hidden. “Translated” into the dimotiki language, they could be appreciated by Greek readers who no longer know the katharévusa. The problem does not arise for those who know ancient Greek and the call katharevusa.